Same Session Transureteral Lithotripsy and Laparoscopy: A Case of Ureteral Stone with Abdominal Forgotten Gauze after Four Years - Mousavi-Bahar, Seyyed-Habibollah; Eslami, Adel (Urology Journal, 2014)
Same Session Transureteral Lithotripsy and Laparoscopy: A Case of Ureteral Stone with Abdominal Forgotten Gauze after Four Years